Zinc oxide (ZnO) nanoparticles as saturable absorber in passively Q-switched fiber laser - Ahmad, Harith; Lee, C.S.J.; Ismail, M.A.; Ali, Z.A.; Reduan, S.A.; Ruslan, N.E.; Ismail, Mohammad Faizal; Harun, Sulaiman Wadi (Elsevier, 2016)
We demonstrate a passively Q-switched erbium-doped fiber laser using zinc oxide (ZnO) nanoparticles thin film as saturable absorber (SA). ZnO exhibits high nonlinear optical response and fast recovery time, fulfilling the requirements of an ideal SA. The nonlinear optical absorption is characterised by modulation depth of 3.5% with saturation intensity of 0.016 MW cm−2. We insert the SA into the laser cavity and obtain stable Q-switched pulse whereby the repetition rate increases from 41.7 kHz to 77.2 kHz while the pulse width decreases from 9.6 μs to 3.0 μs as the pump power is increased from 60 mW to 360 mW. This result suggests that ZnO could be a promising SA for photonic applications.